A resin composition and prepreg and metal foil-clad laminate containing the same
The coordinated combination of resin compositions of specific structures and contents, including maleimide compounds with N-substituted maleimide groups, primary aminoamine compounds, unsaturated polyphenylene ethers and crosslinking agents, is solved The problems of poor dielectric loss tangent performance when used in high-frequency and high-speed electronic products are used, and the effects of low thermal expansion coefficient, high glass transition temperature and high adhesion are achieved.
Patent Information
- Application Number
- CN202111683512.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-12-31
AI Technical Summary
When used in high-frequency and high-speed electronic products, existing resin materials have problems such as poor dielectric loss tangent performance, high cured product brittleness, short storage period and high thermal expansion coefficient.
Resin compositions with specific structures and contents, including maleimide compounds containing at least 2 N-substituted maleimide groups in one molecule and amine compounds containing at least 2 primary amino groups in one molecule The synergistic combination of the addition reactants, unsaturated bond-containing polyphenylene ether and crosslinking agent ensures the total weight of the maleimide compound that is not involved in the addition reaction and the addition reactants with a weight average molecular weight less than 1000. 40-80%.
The resin composition has achieved a low plane thermal expansion coefficient, high glass transition temperature, low dielectric loss tangent, and high adhesion with metal foil, to meet the application needs of high-frequency and high-speed printed circuit boards and electronic equipment.
Smart Images

Figure CN116410595B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of printed circuit boards, and in particular relates to a resin composition and a prepreg and a metal foil-clad laminate containing the same. Background Art
[0002] In recent years, information technology has entered a stage of high-speed signal and high-frequency transmission. In order to match the increasing amount of data processing, the frequency of electronic equipment is getting higher and higher, which puts higher requirements on the electrical performance of the substrate to minimize the loss and delay of high-frequency signals. With the advent of the 5G era, represented by high-frequency RF (such as PA, WiGig, WiHD / 60GHz, etc.), large-size chips, DDR5 (3.2~6.4Gbps) and other applications, higher requirements are placed on the performance of packaging substrate materials: while having a low planar thermal expansion coefficient, it must also have a lower dielectric loss tangent.
[0003] Bismaleimide (BMI) resin is a traditional encapsulation substrate resin system, which has high monomer activity, no molecular release during polymerization, stable finished product performance, and can maintain high physical and mechanical properties in a wide temperature range. CN109825081A discloses a thermosetting resin composition, which includes the following components: a combination of bismaleimide resin and benzoxazine resin or a prepolymer of bismaleimide resin and benzoxazine resin, epoxy resin and active ester; the metal foil laminate prepared by the resin composition has a high glass transition temperature, a low thermal expansion coefficient, a high high temperature modulus and good heat resistance; however, the cured product of the maleimide resin system is brittle, has a short storage period, and has poor dielectric loss tangent performance, thereby limiting its application in high-frequency and high-speed electronic products.
[0004] The current mainstream high-speed low dielectric loss tangent resin system usually includes polyphenylene ether resin. The molecular structure of polyphenylene ether resin contains benzene rings, which give it good physical and mechanical properties, as well as a low dielectric constant and dielectric loss tangent. However, polyphenylene ether resin is a thermoplastic resin, which has the problems of high melting point, poor processing performance, and poor solvent resistance. Therefore, polyphenylene ether needs to be modified in actual use. CN109988298A discloses a modified polyphenylene ether resin, a thermosetting resin composition and its use; the modified polyphenylene ether resin is a resin structure obtained by reacting a low molecular weight double-terminated hydroxyl polyphenylene ether with a diacyl halide or dicarboxylic acid containing a specific structural unit, a monofunctional aromatic phenol or a monofunctional aromatic acyl halide or a monofunctional aromatic carboxylic acid; the prepreg, circuit substrate and laminated film made of the thermosetting resin composition have low dielectric constant, low dielectric loss tangent and good heat resistance; however, the polyphenylene ether resin system containing terminal hydroxyl groups has unreacted hydroxyl groups, which leads to an increase in the water absorption rate of the prepreg or circuit substrate during use, a decrease in moisture and heat resistance, and affects the reliability of the board.
[0005] Polyolefin resin has good performance in toughness and dielectric properties, and combining it with polyphenylene ether resin can improve comprehensive performance. CN111154197A discloses a polyolefin resin composition, including 30-80 parts of polyolefin resin, 1-30 parts of bismaleimide resin, 30-80 parts of polyphenylene ether resin, 0.1-5 parts of initiator, 20-60 parts of inorganic filler, 10-30 parts of flame retardant and 50-120 parts of solvent; the copper-clad laminate made of glass fiber cloth impregnated with the polyolefin resin composition as a resin matrix has a low dielectric constant and dielectric loss tangent, good peel strength, but its glass transition temperature is low, the thermal expansion coefficient is high, and the dimensional stability is poor, which is difficult to meet the performance requirements of high-frequency equipment for packaging substrates.
[0006] Therefore, developing a resin material with excellent dielectric properties, reliability, high adhesion and low thermal expansion coefficient is the research focus in this field. Summary of the invention
[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a resin composition and a prepreg and a metal foil-clad laminate comprising the same, wherein the resin composition has a low planar thermal expansion coefficient, a high glass transition temperature and a low dielectric loss, and has a high adhesion to the metal foil, and is particularly suitable for high-frequency and high-speed packaging by synergistically compounding (A) an addition reactant of a maleimide compound a1 containing at least 2 N-substituted maleimide groups in one molecule and an amine compound a2 containing at least 2 primary amino groups in one molecule, (B) a polyphenylene ether containing an unsaturated bond and (C) a cross-linking agent, wherein the weight of the maleimide compound a1 not participating in the addition reaction and the addition reactant having a weight-average molecular weight of less than 1000 in the component (A) accounts for 40 to 80% of the component (A).
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a resin composition, which comprises the following components in parts by weight: (A) 10 to 70 parts of an addition reaction product of a maleimide compound a1 containing at least 2 N-substituted maleimide groups in one molecule and an amine compound a2 containing at least 2 primary amino groups in one molecule; (B) 10 to 70 parts of a polyphenylene ether containing an unsaturated bond; and (C) 5 to 50 parts of a cross-linking agent.
[0010] The (A) component includes an addition reaction product of a maleimide compound a1 containing at least 2 (e.g., 2, 3 or 4, etc.) N-substituted maleimide groups in one molecule and an amine compound a2 containing at least 2 (e.g., 2, 3, 4 or 5, etc.) primary amino groups in one molecule; the total weight of the maleimide compound a1 not participating in the addition reaction and the addition reaction product with a weight average molecular weight of less than 1000 in the (A) component accounts for 40 to 80% of the (A) component.
[0011] The resin composition provided by the present invention comprises a combination of (A) an addition reaction product of a maleimide compound a1 containing at least 2 N-substituted maleimide groups in one molecule and an amine compound a2 containing at least 2 primary amino groups in one molecule, (B) a polyphenylene ether containing an unsaturated bond, and (C) a crosslinking agent. Wherein, the addition reaction product of the maleimide compound a1 containing at least 2 N-substituted maleimide groups in one molecule and the amine compound a2 containing at least 2 primary amino groups in one molecule and (B) a polyphenylene ether containing an unsaturated bond are used as the main body, and the resin composition solves the defect that low dielectric loss and low thermal expansion coefficient cannot coexist in the prior art through the combination and coordination of the three components in specific weight parts, and gives the resin composition a low planar thermal expansion coefficient, a high glass transition temperature, a low dielectric loss tangent, a high adhesion to metal foil, and good processability, so that it can fully meet the application requirements of high-frequency and high-speed printed circuit boards and electronic equipment.
[0012] In the present invention, the addition reaction product of (A) a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule has high heat resistance, reactivity and low planar thermal expansion coefficient.
[0013] The addition reaction product of the maleimide compound a1 containing at least 2 N-substituted maleimide groups in one molecule and the amine compound a2 containing at least 2 primary amino groups in one molecule (A) is a maleimide mixture, which includes maleimide addition reaction monomers, maleimide addition reaction oligomers or polymers, and also includes maleimide monomers, maleimide oligomers or polymers that do not participate in the addition reaction, wherein the maleimide compounds that do not participate in the addition reaction and the small molecule maleimide addition reactants that participate in the addition reaction constitute the part of the (A) component with a weight average molecular weight less than 1000. The weight of the maleimide compound a1 not participating in the addition reaction and the addition reactant with a weight average molecular weight less than 1000 in the (A) component accounts for 40-80% of the (A) component, such as 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76% or 78%, etc., and the percentage can be obtained by gel chromatography (GPC) test. Because the (A) component contains a specific content of the maleimide compound a1 not participating in the addition reaction and the addition reactant with a weight average molecular weight less than 1000, the resin composition prepared therefrom has excellent fluidity under heating and pressurizing conditions, so that it can be evenly coated on the metal foil, reduce the secondary surface defects of the laminate, and improve the adhesion between the resin composition and the metal foil. If the total weight of the maleimide compound a1 that does not participate in the addition reaction and the addition reactant with a weight average molecular weight of less than 1000 accounts for too high a proportion of the (A) component, the fluidity of the resin composition will be too large, which may easily cause uneven thickness of the laminate and the metal foil-clad laminate and sub-apparent groove defects of the laminate, affecting subsequent processing and use; if the total weight of the maleimide compound a1 that does not participate in the addition reaction and the addition reactant with a weight average molecular weight of less than 1000 accounts for too low a proportion of the (A) component, the fluidity of the resin composition will be reduced, resulting in sub-apparent dry flower defects on the laminate and reduced adhesion between the resin composition and the metal foil.
[0014] The “parts” and “parts by weight” involved in the present invention are all calculated based on solid content and do not include solvents, dispersants, etc.
[0015] In the resin composition provided by the present invention, the addition reaction product of the component (A) of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule is 10 to 70 parts, for example, it can be 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, 48 parts, 50 parts, 52 parts, 55 parts, 58 parts, 60 parts, 62 parts, 65 parts or 68 parts, etc.
[0016] The (B) component contains 10 to 70 parts of polyphenylene ether containing unsaturated bonds, for example, 12, 15, 18, 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48, 50, 52, 55, 58, 60, 62, 65 or 68 parts.
[0017] The cross-linking agent of component (C) is 5 to 50 parts, for example, it can be 6 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts or 48 parts.
[0018] Preferably, the primary amine value of the (A) component is 0.10-1.00 mmol / g, for example, it can be 0.15 mmol / g, 0.20 mmol / g, 0.25 mmol / g, 0.30 mmol / g, 0.35 mmol / g, 0.40 mmol / g, 0.45 mmol / g, 0.50 mmol / g, 0.55 mmol / g, 0.60 mmol / g, 0.65 mmol / g, 0.70 mmol / g, 0.75 mmol / g, 0.85 mmol / g, 0.90 mmol / g or 0.95 mmol / g, etc., and its primary amine value can be obtained by potassium hydrogen phthalate titration test. Since the (A) component contains a specific content of primary amine value, the resin composition prepared therefrom has a low dielectric constant and a low dielectric loss tangent. If the primary amine value is too high, the gelation time of the (A) component will shorten rapidly during storage, thereby affecting the timeliness of the use of the (A) component in the resin composition; if the primary amine value is too low, resin will precipitate from the (A) component during storage, which will also affect the timeliness of the use of the (A) component in the resin composition.
[0019] Preferably, the maleimide compound a1 contains two N-substituted maleimide groups in one molecule, which can give the modified maleimide compound better solubility.
[0020] Preferably, the maleimide compound a1 includes N,N'-ethylenebismaleimide, N,N'-hexamethylenebismaleimide, N,N'-(1,3-phenylene)bismaleimide, N,N'-(1,3-(2-methylphenylene))bismaleimide, N,N'-(1,3-(4-methylphenylene))bismaleimide, N,N'-(1,4-phenylene)bismaleimide, bis(4-maleimidophenyl)methane, bis(3-methyl-4-maleimidophenyl)methane, bis(3,5-dimethyl-4-maleimidophenyl)methane, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane methane, bis(3-ethyl-4-maleimidophenyl)methane, bis(3,5-diethyl-4-maleimidophenyl)methane, bis(4-maleimidophenyl)ether, bis(4-maleimidophenyl)ketone, bis(4-maleimidocyclohexyl)methane, 1,4-bis(4-maleimidophenyl)cyclohexane, 1,4-bis(maleimidomethyl)cyclohexane, 1,4-bis(maleimidomethyl)benzene, 1,3-bis(4-maleimidophenoxy)benzene, 1,3-bis(3-maleimidophenoxy)benzene, bis(4-(3-maleimidophenoxy)phenyl)methane, bis(4-(4-maleimidophenoxy) 1,1-bis(4-(3-maleimidophenoxy)phenyl)ethane, 1,1-bis(4-(4-maleimidophenoxy)phenyl)ethane, 1,2-bis(4-(3-maleimidophenoxy)phenyl)ethane, 1,2-bis(4-(4-maleimidophenoxy)phenyl)ethane, 2,2-bis(4-(3-maleimidophenoxy)phenyl)propane, 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, 2,2-bis(4-(3-maleimidophenoxy)phenyl)butane, 2,2-bis(4-(4-maleimidophenoxy)phenyl)butane, 4,4'- Any one or a combination of at least two of bis(3-maleimidophenoxy)biphenyl, 4,4'-bis(4-maleimidophenoxy)biphenyl, bis(4-(3-maleimidophenoxy)phenyl)ketone, bis(4-(4-maleimidophenoxy)phenyl)ketone, bis(4-(3-maleimidophenoxy)phenyl)ether or bis(4-(4-maleimidophenoxy)phenyl)ether, and further preferably any one or a combination of at least two of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, bis(4-maleimidophenyl)methane or 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane.
[0021] Preferably, the amine compound a2 includes a siloxane compound containing at least two primary amino groups, diaminobenzidine, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diethyl-4,4'-diaminobiphenyl, diaminodiphenylmethane, 3,3'-dimethoxy-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, diaminodiphenyl ether, 3,3'-dimethoxy-4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminodiphenyl ether, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenyl ether, 3,3'-diethyl-4,4'-diaminodiphenyl ether, 3,3'-diethyl-5,5'-diethyl -4,4'-diaminodiphenyl ether, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 2,2-bis(4-(3-aminophenoxy)phenyl)propane, 4,4'-bis(4-aminophenoxy)biphenyl, 1,4-bis(4-aminophenoxy)benzene, 2,2'-dimethyl-4,4'-diaminobiphenyl or 4,4'-diamino-3,3'-dihydroxybiphenyl, or any one or a combination of at least two thereof; further Preferred is any one of a siloxane compound containing at least two primary amino groups, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, or 2,2-bis(4-(4-aminophenoxy)phenyl)propane, or a combination of at least two thereof.
[0022] Preferably, the amine compound a2 includes a siloxane compound having two primary amino groups in one molecule, and more preferably includes a siloxane compound having two primary amino groups at the molecular end.
[0023] Preferably, based on 100 parts by weight of the total amount of the component (A), the component (B) and the component (C), the amount of the siloxane compound containing two primary amino groups is 1 to 30 parts, for example, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts or 28 parts, etc., more preferably 2 to 15 parts, which can enable the resin composition to have a low planar thermal expansion coefficient and good fluidity.
[0024] As a preferred technical solution of the present invention, the amine compound a2 includes a siloxane compound containing two primary amino groups, and a resin composition with a low planar expansion coefficient can be obtained. The siloxane compound containing two primary amino groups can use commercially available products, exemplarily including but not limited to: PAM-E (side chain methyl type, functional group equivalent 130g / mol), KF-8010 (side chain methyl type, functional group equivalent 430g / mol), X-22-161A (side chain methyl type, functional group equivalent 800g / mol), X-22-161B (side chain methyl type, functional group equivalent Any one of KF-8012 (side chain methyl type, functional group equivalent weight 1500 g / mol), KF-8008 (side chain methyl type, functional group equivalent weight 5700 g / mol), X-22-1660B-3 (side chain phenyl type, functional group equivalent weight 2200 g / mol) or X-22-9409 (side chain phenyl type, functional group equivalent weight 670 g / mol) or a combination of at least two thereof.
[0025] The addition reaction of the maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and the amine compound a2 containing at least two primary amino groups in one molecule is preferably carried out in an organic solvent; the type of the organic solvent is not particularly limited, and propylene glycol monomethyl ether is more preferably used.
[0026] In the present invention, the temperature of the addition reaction of the maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and the amine compound a2 containing at least two primary amino groups in one molecule is not particularly limited, as long as the maleimide compound a1 and the amine compound a2 react. As a preferred technical scheme of the present invention, from the perspective of reaction rate and solvent boiling point, preferably, the temperature of the addition reaction is 100-130°C, for example, 102°C, 105°C, 108°C, 110°C, 112°C, 115°C, 118°C, 120°C, 122°C, 125°C or 128°C, etc.
[0027] In the present invention, the addition reaction time of the maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and the amine compound a2 containing at least two primary amino groups in one molecule is not particularly limited. Preferably, the addition reaction time is 2 to 10 hours, for example, it can be 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, etc., and more preferably 3 to 8 hours.
[0028] Preferably, the (B) component is a polyphenylene ether containing an unsaturated group at the terminal.
[0029] Preferably, the unsaturated group includes any one of vinylbenzyl, vinylphenyl or acrylate groups, or a combination of at least two of them.
[0030] In the present invention, the structural formula of the vinylbenzyl group is Dashed lines represent the attachment sites of the groups.
[0031] The structural formula of the acrylate group is The dotted line represents the attachment site of the group; R3 is selected from hydrogen, C1-C20 (e.g., C2, C3, C4, C5, C6, C7, C8, C9, C10, C12, C14, C16, C18 or C19, etc.) straight chain or branched alkyl, and is more preferably hydrogen, C1-C10 straight chain or branched alkyl.
[0032] The acrylic acid ester group is further preferably an acrylate group or a methacrylate group.
[0033] As a preferred technical solution of the present invention, the unsaturated bond-containing polyphenylene ether of component (B) is a polyphenylene ether containing a vinyl benzyl group at the end, which is more conducive to improving the dielectric properties and heat resistance of the resin composition. The polyphenylene ether containing a vinyl benzyl group at the end can be a commercially available product, exemplarily including but not limited to: OPE-2st 1200 (number average molecular weight M n 1200) and / or OPE-2st 2200 (number average molecular weight M n is 2200) etc.
[0034] In the present invention, the (C) crosslinking agent is not particularly limited, as long as it can cause the composition to undergo a crosslinking reaction. As a preferred technical solution of the present invention, the (C) crosslinking agent includes a crosslinking agent and / or a cyanate ester having a carbon-carbon unsaturated double bond in the molecule.
[0035] Preferably, the crosslinking agent having a carbon-carbon unsaturated double bond in the molecule includes any one or a combination of at least two of a multifunctional vinyl compound, an allyl compound, an acrylate compound, a trialkenyl isocyanurate compound, other maleimide compounds, an acenaphthylene compound or polybutadiene.
[0036] Preferably, the trialenyl isocyanurate compound includes triallyl isocyanurate.
[0037] Preferably, the acrylate compound includes an acrylate compound having a structure as shown in Formula I:
[0038]
[0039] Wherein, R1 is each independently selected from C1~C20 (for example, C2, C3, C4, C5, C6, C7, C8, C9, C10, C12, C14, C16, C18 or C19, etc.) straight chain or branched alkylene; R2 is each independently selected from hydrogen, C1~C20 (for example, C2, C3, C4, C5, C6, C7, C8, C9, C10, C12, C14, C16, C18 or C19, etc.) straight chain or branched alkyl.
[0040] Preferably, the acrylic ester compound crosslinking agent (C) having the structure shown in Formula I can synergistically enhance the effect with the components (A) and (B) to further improve the cohesive strength of the resin composition and enhance the adhesion to the metal foil.
[0041] As a preferred technical solution of the present invention, based on the total amount of the (A) component, the (B) component and the (C) component as 100 parts by weight, the amount of the (A) component is 10 to 60 parts, for example, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, 48 parts, 50 parts, 52 parts, 55 parts or 58 parts, etc.
[0042] If the content of component (A) is too low, the glass transition temperature of the resin composition will be reduced; if the content of component (A) is too high, the dielectric loss of the resin composition will be increased, affecting the dielectric properties.
[0043] Preferably, based on 100 parts by weight of the total amount of the (A) component, the (B) component and the (C) component, the amount of the (B) component is 10 to 60 parts, for example, 12, 15, 18, 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48, 50, 52, 55 or 58 parts, etc.
[0044] If the content of component (B) is too high, the adhesion between the resin composition and the metal foil will decrease, and the glass transition temperature of the resin composition will decrease, affecting the reliability of the laminate; if the content of component (B) is too low, the dielectric properties of the resin composition will be affected, making it difficult to meet the requirements of high-speed applications.
[0045] As a preferred technical solution of the present invention, based on the total amount of the (A) component, the (B) component and the (C) component as 100 parts by weight, the amount of the (C) component is 5 to 30 parts, for example, 6 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts or 28 parts.
[0046] If the content of component (C) is too low, the crosslinking density of the resin composition decreases and the glass transition temperature decreases; if the amount of component (C) is too high, the dielectric loss tangent of the resin composition increases. At the same time, the curing reaction is insufficient due to excessive unreacted groups, affecting the reliability of the resin composition, laminated board, metal foil-clad laminated board and printed circuit board.
[0047] Preferably, the resin composition further comprises 5 to 30 parts of polyolefin resin by weight, for example, the polyolefin resin may be 6 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts or 28 parts.
[0048] As a preferred technical solution of the present invention, the polyolefin resin helps to improve the dielectric properties of the resin composition. However, if the content of the polyolefin resin is too high, the adhesion between the resin composition and the metal foil is reduced, and at the same time, the melt fluidity of the resin composition is reduced, which is not conducive to preparing a resin composition with uniform thickness.
[0049] Preferably, the polyolefin resin includes a styrene copolymer. A styrene copolymer is, for example, a copolymer including an olefin structural unit and a styrene structural unit. The olefin structural unit is derived from an olefin monomer, such as a structural unit derived from butadiene, a structural unit derived from isoprene, etc.; the styrene structural unit is derived from a styrene monomer, such as a structural unit derived from styrene, a structural unit derived from styrene with a substituent, etc. In addition to containing structural units derived from olefin structural units and styrene structural units, styrene copolymers may also contain structural units other than olefin structural units and styrene structural units, such as structural units derived from epoxy groups, structural units derived from amino groups, structural units derived from maleic anhydride, etc.
[0050] The styrenic copolymer may be a random copolymer or a block copolymer. If the styrenic copolymer is a random copolymer, the styrenic copolymer is a copolymer in which a plurality of olefin structural units and a plurality of styrenic structural units are randomly arranged. If the styrenic copolymer is a block copolymer, the styrenic copolymer is a copolymer in which one or more olefin blocks and one or more styrenic blocks are arranged. The olefin block is composed of a plurality of olefin structural units, and the styrenic block is composed of a plurality of styrenic structural units.
[0051] The structural unit derived from olefin of the polyolefin resin may be hydrogenated or partially hydrogenated. Based on the consideration of dielectric properties, the structural unit derived from olefin of the polyolefin resin may be hydrogenated.
[0052] The polyolefin resin may be a commercially available product, illustratively including but not limited to: any one of Ricon 153 (butadiene copolymer, Cray Valley), Ricon 100 (butadiene-styrene copolymer, Cray Valley), Ricon 181 (butadiene-styrene copolymer, Cray Valley), Tuftec H1051 (hydrogenated styrene-butadiene copolymer, with a styrene content of 42% by mass, Asahi Kasei Chemicals Corporation) or Tuftec M1913 (hydrogenated styrene-butadiene copolymer with maleic anhydride structural units, with a styrene content of 30% by mass, Asahi Kasei Chemicals Corporation) or a combination of at least two thereof.
[0053] Preferably, the resin composition further includes 0.01 to 5 parts of a curing accelerator by weight, for example, the curing accelerator may be 0.03 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 4.8 parts, etc.
[0054] Preferably, the curing accelerator includes any one of an acidic curing accelerator, an organic phosphorus curing accelerator, an imidazole curing accelerator, a pyridine curing accelerator, an amine curing accelerator, a peroxide or an organic metal salt, or a combination of at least two thereof.
[0055] For example, the acidic curing accelerator includes p-toluenesulfonic acid, etc.; the organophosphorus curing accelerator includes triphenylphosphine, etc.; the imidazole curing accelerator includes imidazole or imidazole derivatives (such as 2-ethyl-4-methylimidazole); the pyridine curing accelerator includes pyridine or pyridine derivatives (such as 4-dimethylaminopyridine); the amine curing accelerator includes secondary amine compounds, tertiary amine compounds or quaternary ammonium salts; the peroxide includes diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexyne-3, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane or α,α'-bis(tert-butylperoxy)diisopropylbenzene, etc.; the organic metal salt includes zinc naphthenate, cobalt naphthenate, tin octoate or cobalt octoate, etc. The curing accelerator can be used alone or in combination of at least two.
[0056] Preferably, the resin composition further comprises 5 to 250 parts of inorganic fillers by weight, for example, the inorganic filler can be 8 parts, 10 parts, 20 parts, 30 parts, 50 parts, 70 parts, 90 parts, 100 parts, 110 parts, 130 parts, 150 parts, 170 parts, 190 parts, 200 parts, 210 parts or 230 parts, etc. The inorganic filler helps to improve the heat resistance, moisture and heat resistance and mechanical properties of the resin composition and reduce the thermal expansion coefficient. If the amount of inorganic filler is too much, the dielectric loss tangent of the resin composition will increase, which is not conducive to signal transmission.
[0057] The present invention is not particularly limited to the type of inorganic filler, and exemplarily includes: any one or at least two combinations of silicon dioxide, aluminum hydroxide, magnesium hydroxide, boehmite, molybdenum oxide, zinc oxide, zinc molybdate, zinc borate, zinc stannate, titanium dioxide, strontium titanate, barium titanate, barium sulfate, clay, kaolin, talc, mica, boron nitride, aluminum nitride, silicon carbide, aluminum oxide, composite silicon powder, glass powder, short glass fiber or hollow glass. In order to make the resin composition have higher heat resistance, moisture and heat resistance and dimensional stability, it is preferably any one or at least two combinations of silicon dioxide, aluminum hydroxide, magnesium hydroxide, boehmite, boron nitride, aluminum nitride, silicon carbide, aluminum oxide, composite silicon powder, glass powder, short glass fiber or hollow glass. Wherein, the silicon dioxide can be crystalline silica, fused silica, amorphous silica, spherical silica or hollow silica, etc., and more preferably spherical silica.
[0058] The average particle size of the inorganic filler (D 50 ) is not particularly limited, but from the perspective of dispersibility, the average particle size (D 50) is preferably 0.01-20 microns, for example 0.02 micron, 0.05 micron, 0.1 micron, 0.2 micron, 0.8 micron, 1.5 micron, 2.1 micron, 2.6 micron, 3.5 micron, 4.5 micron, 5.2 micron, 5.5 micron, 6 micron, 6.5 micron, 7 micron, 7.5 micron, 8 micron, 8.5 micron, 9 micron, 9.5 micron, 12 micron, 13.5 micron, 15 micron, 17.5 micron, 18 micron, 19.5 micron, more preferably 0.1-10 micron. Inorganic fillers of different types, different particle size distributions or different average particle diameters can be used alone or in combination as needed.
[0059] Preferably, the resin composition further comprises 0.01 to 10 parts of a coupling agent by weight, for example, the coupling agent may be 0.03, 0.05, 0.1, 0.3, 0.5, 1, 2, 3, 4, 5, 6, 7, 8 or 9 parts, etc., and 0.1 to 6 parts of a coupling agent are further preferred; the coupling agent helps to improve the compatibility of the inorganic filler with the resin composition.
[0060] Preferably, the coupling agent comprises a silane coupling agent.
[0061] The present invention does not particularly limit the type of silane coupling agent, and illustratively can be: any one of epoxy silane coupling agent, amino silane coupling agent, vinyl silane coupling agent, styrene silane coupling agent, isobutylene silane coupling agent, acryl silane coupling agent, urea silane coupling agent, mercapto silane coupling agent, chloropropyl silane coupling agent, sulfide silane coupling agent or isocyanate silane coupling agent, or a combination of at least two thereof.
[0062] Preferably, the resin composition further comprises a flame retardant. The flame retardant is not particularly limited, and can be selected from halogen or non-halogen flame retardants that are soluble or insoluble in an organic solvent. Exemplarily, the non-halogen flame retardant includes an inorganic phosphorus flame retardant, an organic phosphorus flame retardant, a metal hydrate, and the like.
[0063] From the perspective of environmental issues and excellent dielectric properties, the flame retardant is preferably an organophosphorus flame retardant. Exemplarily, the organophosphorus flame retardant includes aromatic phosphates, monosubstituted phosphonic acid diesters, disubstituted phosphinates, metal salts of disubstituted phosphinates, organic nitrogen-containing phosphorus compounds, cyclic organophosphorus compounds, and the like.
[0064] For example, the aromatic phosphates include triphenyl phosphate, tricresyl phosphate, tri(xylene) phosphate, cresyl diphenyl phosphate, cresyl di-2,6-xylene phosphate, resorcinol bis(diphenyl phosphate), 1,3-phenylene bis(di(2,6-dimethylphenyl) phosphate), 4,4'-biphenyl bis(di(2,6-dimethylphenyl) phosphate), bisphenol A-bis(di(2,6-dimethylphenyl) phosphate), bisphenol A-bis(diphenyl phosphate), 1,3-phenylene bis(diphenyl phosphate), etc.; the monosubstituted phosphonic acid diesters include divinyl phenylphosphonate, diallyl phenylphosphonate, bis(1-butenyl) phenylphosphonate, etc.; the disubstituted phosphinates include Phenyl diphenylphosphinate, methyl diphenylphosphinate, etc.; the metal salt of the disubstituted phosphinate includes metal salts of dialkylphosphinate, metal salts of diallylphosphinate, metal salts of divinylphosphinate, metal salts of diarylphosphinate, etc.; the organic nitrogen-phosphorus compound includes phosphazene compound, melamine phosphate, melamine polyphosphate, melamine pyrophosphate, etc.; the cyclic organic phosphorus compound includes 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-phenyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10 oxide, etc.
[0065] The flame retardants may be used alone or in combination of at least two kinds.
[0066] There is no particular restriction on the amount of the flame retardant. Preferably, when a phosphorus-based flame retardant is used in the resin composition of the present invention, the amount of the flame retardant is preferably 0.2 to 5 parts by weight, more preferably 0.3 to 3 parts by weight, and further preferably 0.5 to 3 parts by weight, based on 100 parts by weight of the total amount of the (A) component, the (B) component, the (C) component, and the flame retardant. When the weight of phosphorus atoms is within this range, a good balance can be achieved in flame retardancy, processability, and heat resistance.
[0067] For the purpose of preparation and processing, the resin composition further includes a solvent. The amount of the solvent is not limited, as long as the components in the resin composition can be dissolved and dispersed and do not separate during mixing.
[0068] The type of the solvent is not particularly limited, and includes any one or a combination of at least two of alcohol solvents, ether solvents, aromatic hydrocarbon solvents, ester solvents, ketone solvents or nitrogen-containing solvents, preferably any one or a combination of at least two of acetone, butanone, methyl ethyl ketone, cyclohexanone, toluene or xylene.
[0069] In another aspect, the present invention provides a prepreg, comprising a substrate, and the resin composition according to the first aspect attached to the substrate by impregnation and drying.
[0070] The present invention has no particular limitation on the substrate. Preferably, the substrate includes any one of glass fiber cloth, organic fiber cloth or glass fiber paper.
[0071] The glass fiber cloth includes Q-glass fiber cloth, E-glass fiber cloth, D-glass fiber cloth, L-glass fiber cloth, M-glass fiber cloth, S-glass fiber cloth, T-glass fiber cloth or NE-glass fiber cloth, etc.
[0072] The organic fiber cloth includes polyimide fiber cloth, polyamide fiber cloth, polyester fiber cloth, polyphenylene ether fiber cloth or liquid crystal polymer fiber cloth.
[0073] Illustratively, the method for preparing the prepreg is: impregnating a substrate with a resin glue of the resin composition, and then drying to obtain the prepreg.
[0074] Preferably, the solvent in the resin glue is not particularly limited, and is further preferably any one of acetone, butanone, methyl ethyl ketone, cyclohexanone, toluene or xylene, or a combination of at least two thereof.
[0075] Preferably, the drying temperature is 100-180°C, for example, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C or 175°C, etc.
[0076] Preferably, the drying time is 1 to 10 min, for example, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min or 9 min.
[0077] In another aspect, the present invention provides a metal foil-clad laminate, comprising at least one prepreg as described above, and a metal foil disposed on one side or both sides of the prepreg.
[0078] The metal foil may be copper foil, aluminum foil, nickel foil or alloy foil; preferably, the metal foil is copper foil.
[0079] Preferably, the number of prepregs in the metal foil-clad laminate is 1 to 20, for example, 1, 3, 5, 7, 9, 10, 11, 13, 15, 17 or 19.
[0080] Exemplarily, the preparation method of the metal-clad laminate is: laminating metal foil on one side or both sides of a prepreg, curing, and obtaining the metal-clad laminate; or, stacking at least two prepregs, and then laminating metal foil on one side or both sides of the stacked prepregs, curing, and obtaining the metal-clad laminate.
[0081] Preferably, the curing is carried out in a press.
[0082] Preferably, the curing temperature is 200-250°C, for example, 205°C, 210°C, 212°C, 215°C, 218°C, 220°C, 223°C, 225°C, 228°C, 230°C, 235°C, 240°C or 245°C, etc.
[0083] Preferably, the curing pressure is 10-60 kg / cm 2 , for example 15kg / cm 2 , 20kg / cm 2 , 25kg / cm 2 、30kg / cm 2 、35kg / cm 2 , 40kg / cm 2 , 45kg / cm 2 , 50kg / cm 2 or 55kg / cm 2 wait.
[0084] Preferably, the curing time is 30 to 180 min, for example, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min or 175 min, etc.
[0085] In another aspect, the present invention provides a printed circuit board, comprising at least one prepreg as described above or one metal foil-clad laminate as described above.
[0086] Compared with the prior art, the present invention has the following beneficial effects:
[0087] The resin composition provided by the present invention comprises (A) an addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule, (B) a polyphenylene ether containing an unsaturated bond and (C) a crosslinking agent, wherein the weight of the maleimide compound a1 not participating in the addition reaction and the addition reaction product with a weight average molecular weight less than 1000 in the component (A) accounts for 40 to 80% of the component (A). By selecting and compounding three components with specific structures and contents, the resin composition has a low planar thermal expansion coefficient, a high glass transition temperature, a low dielectric loss tangent, a high adhesion to a metal foil and good processability. The metal foil-clad laminate prepared from the prepreg containing the resin composition has a glass transition temperature of 218 to 295° C., a planar thermal expansion coefficient as low as 7 to 13 ppm / ° C., a dielectric constant of 3.85 to 4.31 at 10 GHz, a dielectric loss tangent of ≤0.0060, a peel strength of 0.45 to 0.65 N / mm, a flat and uniform laminate, and no dry spots or grooves on the surface. The laminate has excellent dielectric properties, high adhesion to the metal foil, dimensional stability and processability, is particularly suitable for high-speed packaging, and can fully meet the application requirements of high-frequency and high-speed printed circuit boards and electronic equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0088] Figure 1 This is a secondary optical picture of the laminate obtained in Comparative Example 2. DETAILED DESCRIPTION
[0089] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0090] Preparation Example 1
[0091] An addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule (hereinafter referred to as BMI A1), the preparation method is as follows:
[0092] In a three-necked flask equipped with a thermometer, a stirring paddle and a reflux condenser, 9 parts by weight of a siloxane compound containing two primary amino groups (X-22-161B of Shin-Etsu Chemical Co., Ltd.), 1 part by weight of an amine compound containing two primary amino groups (Kayahard AA of Nippon Kayaku Kogyo Co., Ltd., 3,3'-diethyl-4,4'-diaminodiphenylmethane), 30 parts by weight of a maleimide compound (BMI-4000 of Yamato Chemical Co., Ltd., 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane) and 40 parts by weight of propylene glycol monomethyl ether were added. The temperature was raised to 115° C. with stirring and then kept warm for continuous reaction. During the reaction, the weight average molecular weight of the addition reactant (BMI A1) was monitored by gel chromatography (GPC, with tetrahydrofuran as the mobile phase). When BMI The reaction was stopped when the weight of the maleimide compound not participating in the addition reaction and the addition reactant with a weight average molecular weight less than 1000 in A1 accounted for 71%. The primary amine value of BMI A1 was measured by acid-base titration method to be 0.22 mmol / g.
[0093] Preparation Example 2
[0094] An addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule (hereinafter referred to as BMI A2), prepared by the following method:
[0095] In a three-necked flask equipped with a thermometer, a stirring paddle and a reflux condenser, 4 parts by weight of an amine compound containing two primary amino groups (BAPP of Wakayama Seika Industries Co., Ltd., 2,2-bis(4-(4-aminophenoxy)phenyl)propane), 36 parts by weight of a maleimide compound (BMI-4000 of Yamato Chemical Industries Co., Ltd., 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane) and 40 parts by weight of propylene glycol monomethyl ether were added, and the temperature was raised to 115° C. with stirring and then kept warm for continuous reaction. During the reaction, the weight average molecular weight of the addition reactant (BMI A2) was monitored by gel chromatography (GPC, with tetrahydrofuran as the mobile phase). The reaction was stopped when the total weight of the maleimide compound not participating in the addition reaction and the addition reactant with a weight average molecular weight of less than 1000 in BMI A2 accounted for 71%. The primary amine value of BMI A2 was measured by acid-base titration and was 0.22mmol / g.
[0096] Preparation Example 3
[0097] An addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule (hereinafter referred to as BMI A3), prepared by the following method:
[0098] In a three-necked flask equipped with a thermometer, a stirring paddle and a reflux condenser, 9.5 parts by weight of a siloxane compound containing two primary amino groups (X-22-161A of Shin-Etsu Chemical Co., Ltd.), 1.5 parts by weight of an amine compound containing two primary amino groups (Kayahard AA of Nippon Kayaku Kogyo Co., Ltd., 3,3'-diethyl-4,4'-diaminodiphenylmethane), 29 parts by weight of a maleimide compound (BMI-1000 of Yamato Chemical Co., Ltd., bis(4-maleimidophenyl)methane) and 40 parts by weight of propylene glycol monomethyl ether were added, the temperature was raised to 115° C. with stirring and then kept warm for continuous reaction. During the reaction, the weight average molecular weight of the addition reactant (BMI A3) was monitored by gel chromatography (GPC, with tetrahydrofuran as the mobile phase). When BMI The reaction was stopped when the weight of the maleimide compound not participating in the addition reaction and the addition reactant with a weight average molecular weight less than 1000 in A3 accounted for 60%. The primary amine value of BMI A3 was measured by acid-base titration method to be 0.42 mmol / g.
[0099] Preparation Example 4
[0100] An addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule (hereinafter referred to as BMI A4), prepared by the following method:
[0101] In a three-necked flask equipped with a thermometer, a stirring paddle and a reflux condenser, 14 parts by weight of a siloxane compound containing two primary amino groups (X-22-161A of Shin-Etsu Chemical Co., Ltd.), 3 parts by weight of an amine compound containing two primary amino groups (BAPP of Wakayama Seika Kogyo Co., Ltd., 2,2-bis(4-(4-aminophenoxy)phenyl)propane), 23 parts by weight of a maleimide compound (BMI-4000 of Yamato Chemical Co., Ltd., 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane) and 40 parts by weight of propylene glycol monomethyl ether were added, the temperature was raised to 115° C. with stirring and then kept warm for continuous reaction. During the reaction, the weight average molecular weight of the addition reactant (BMI A4) was monitored by gel chromatography (GPC, with tetrahydrofuran as the mobile phase). When BMI The reaction was stopped when the weight of the maleimide compound not participating in the addition reaction and the addition reactant with a weight average molecular weight less than 1000 in A4 accounted for 48%. The primary amine value of BMI A4 was measured by acid-base titration method to be 0.76 mmol / g.
[0102] Preparation Example 5
[0103] An addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule (hereinafter referred to as BMI A5), prepared by the following method:
[0104] In a three-necked flask equipped with a thermometer, a stirring paddle and a reflux condenser, 2 parts by weight of a modified siloxane compound containing two primary amino groups (X-22-161B of Shin-Etsu Chemical Co., Ltd.), 12 parts by weight of an amine compound containing two primary amino groups (Kayahard AA of Nippon Kayaku Kogyo Co., Ltd., 3,3'-diethyl-4,4'-diaminodiphenylmethane), 26 parts by weight of a maleimide compound (BMI-4000 of Yamato Chemical Co., Ltd., 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane) and 40 parts by weight of propylene glycol monomethyl ether were added, the temperature was raised to 110° C. with stirring and then kept warm for continuous reaction. During the reaction, the weight average molecular weight of the addition reactant (BMI A5) was monitored by gel chromatography (GPC, with tetrahydrofuran as the mobile phase). When BMI The reaction was stopped when the weight of the maleimide compound not participating in the addition reaction and the addition reactant with a weight average molecular weight less than 1000 in A5 accounted for 45%. The primary amine value of BMI A5 was measured by acid-base titration method to be 1.10 mmol / g.
[0105] Preparation Example 6
[0106] An addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule (hereinafter referred to as BMI A6), prepared by the following method:
[0107] In a three-necked flask equipped with a thermometer, a stirring paddle and a reflux condenser, 5 parts by weight of a modified siloxane compound containing two primary amino groups (X-22-161B of Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of an amine compound containing two primary amino groups (Kayahard AA of Nippon Kayaku Kogyo Co., Ltd., 3,3'-diethyl-4,4'-diaminodiphenylmethane), 34.5 parts by weight of a maleimide compound (BMI-4000 of Yamato Chemical Co., Ltd., 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane) and 40 parts by weight of propylene glycol monomethyl ether were added, the temperature was raised to 120° C. with stirring and then kept warm for continuous reaction. During the reaction, the weight average molecular weight of the addition reactant (BMI A6) was monitored by gel chromatography (GPC, with tetrahydrofuran as the mobile phase). When BMI The reaction was stopped when the weight of the maleimide compound not participating in the addition reaction and the addition reactant with a weight average molecular weight less than 1000 in A6 accounted for 75%. The primary amine value of BMI A6 was measured by acid-base titration method to be 0.08 mmol / g.
[0108] Comparative Preparation Example 1
[0109] An addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule (hereinafter referred to as BMI C1), the preparation method is as follows:
[0110] In a three-necked flask equipped with a thermometer, a stirring paddle and a reflux condenser, 20 parts by weight of a siloxane compound containing two primary amino groups (X-22-161B of Shin-Etsu Chemical Co., Ltd.), 1 part by weight of an amine compound containing two primary amino groups (Kayahard AA of Nippon Kayaku Kogyo Co., Ltd., 3,3'-diethyl-4,4'-diaminodiphenylmethane), 19 parts by weight of a maleimide compound (BMI-4000 of Yamato Chemical Co., Ltd., 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane) and 40 parts by weight of propylene glycol monomethyl ether were added. The temperature was raised to 115° C. with stirring and then kept warm for continuous reaction. During the reaction, the weight average molecular weight of the addition reactant (BMI C1) was monitored by gel chromatography (GPC, with tetrahydrofuran as the mobile phase). When BMI The reaction was stopped when the weight of the maleimide compound not participating in the addition reaction and the addition reactant with a weight average molecular weight less than 1000 in C1 accounted for 35%. The primary amine value of BMI C1 was measured by acid-base titration method to be 0.46 mmol / g.
[0111] Comparative Preparation Example 2
[0112] An addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule (hereinafter referred to as BMI C2), prepared by the following method:
[0113] In a three-necked flask equipped with a thermometer, a stirring paddle and a reflux condenser, 6 parts by weight of a modified siloxane compound containing two primary amino groups (X-22-161B of Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of an amine compound containing two primary amino groups (Kayahard AA of Nippon Kayaku Kogyo Co., Ltd., 3,3'-diethyl-4,4'-diaminodiphenylmethane), 33.5 parts by weight of a maleimide compound (BMI-4000 of Yamato Chemical Co., Ltd., 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane) and 40 parts by weight of propylene glycol monomethyl ether were added, the temperature was raised to 115° C. with stirring and then kept warm for continuous reaction. During the reaction, the weight average molecular weight of the addition reactant (BMI C2) was monitored by gel chromatography (GPC, with tetrahydrofuran as the mobile phase). When BMI The reaction was stopped when the weight of the maleimide compound not participating in the addition reaction and the addition reactant with a weight average molecular weight less than 1000 in C2 accounted for 85%. The primary amine value of BMI C2 was measured by acid-base titration method to be 0.14 mmol / g.
[0114] The experimental materials involved in the following embodiments and comparative examples of the present invention include:
[0115] 1) Component (A): an addition reaction product of a maleimide compound a1 having at least two N-substituted maleimide groups in one molecule and an amine compound a2 having at least two primary amino groups in one molecule
[0116] BMI A1, Preparation Example 1
[0117] BMI A2, Preparation Example 2
[0118] BMI A3, Preparation Example 3
[0119] BMI A4, Preparation Example 4
[0120] BMI A5, Preparation Example 5
[0121] BMI A6, Preparation Example 6
[0122] BMI C1, Comparative Preparation Example 1
[0123] BMI C2, Comparative Preparation Example 2
[0124] 2) Component (B): polyphenylene ether containing unsaturated bonds
[0125] OPE-2st 2200, polyphenylene ether containing vinyl benzyl groups at the end, Mitsubishi Chemical Corporation
[0126] SA-9000, Polyphenylene ether containing methacrylate groups at the end, Saudi Basic Industries Corporation
[0127] 3) Component (C): Crosslinking agent
[0128] NK ESTER DCP, Tricyclodecane dimethanol methacrylate, Shin-Nakamura Chemical Industry Co., Ltd.
[0129] FARIDA TAIC-A, Triallyl isocyanurate, Hunan Fangruida Technology Co., Ltd.
[0130] 4) Polyolefin resin
[0131] Tuftec H1051, Hydrogenated styrene-butadiene copolymer, Asahi Kasei Chemicals Corporation
[0132] Tuftec M1913, Hydrogenated styrene-butadiene copolymer with maleic anhydride structural units, Asahi Kasei Chemicals Corporation
[0133] 5) Curing accelerator
[0134] Triginox 311, 3,3,5,7,7-pentamethyl-1,2,4-trioxypropane, Akzo Nobel, USA
[0135] 6) Inorganic fillers
[0136] SC2300-SVJ, spherical silica surface treated with vinyl silane coupling agent, median particle size D 50 0.5μm, Japan Admatechs Co., Ltd.
[0137] 7) Coupling agent
[0138] KBM-573, N-phenyl-3-aminopropyltrimethoxysilane, Shin-Etsu Corporation
[0139] Example 1
[0140] This embodiment provides a resin composition, which includes the following components in parts by weight: (A) 40 parts of BMI A1, (B) 40 parts of unsaturated bond-containing polyphenylene ether OPE-2st 2200, (C) 20 parts of tricyclodecane dimethanol methacrylate NK ESTERDCP, 2 parts of curing accelerator Triginox 311, 2 parts of coupling agent KBM-573, and 130 parts of inorganic filler SC2300-SVJ.
[0141] This embodiment also provides a metal foil-clad laminate, and the specific preparation method is as follows:
[0142] (1) The resin composition provided in this embodiment, toluene and butanone are mixed, fully dissolved and evenly dispersed to obtain a resin glue solution with a solid content of 60%;
[0143] (2) impregnating glass fiber cloth (3313 manufactured by Huber, Taiwan, China) with the resin glue obtained in step (1), heating and drying in a blast oven at 130° C. for 4 min to convert the resin composition in a varnish state into a resin composition in a semi-cured state, thereby obtaining a prepreg having a thickness controlled to be 0.10 mm;
[0144] (3) Two (or eight) prepregs obtained in step (2) are stacked, and electrolytic copper foil with a thickness of 18 μm is pressed on the upper and lower sides thereof at 220°C and 45 kg / cm 2 After curing for 2 hours, a copper-clad laminate with a core board thickness of 0.20 mm (or 0.80 mm) was obtained.
[0145] After etching the copper foil of the copper-clad laminate, a laminate with a thickness of 0.20 mm (or 0.80 mm) is obtained.
[0146] Examples 2 to 11, Comparative Examples 1 to 9
[0147] A resin composition, the components and contents of which are shown in Table 1 and Table 2; the dosage units of each component in Table 1 and Table 2 are all "parts".
[0148] Table 1
[0149]
[0150]
[0151] Table 2
[0152]
[0153] The above resin composition was made into a metal foil-clad laminate according to the method in Example 1. The properties of the laminate and the test methods of the experimental materials are as follows:
[0154] (1) Glass transition temperature T g : A laminate with a length of 60 mm, a width of 10 mm, and a thickness of 0.80 mm was taken as a sample and measured using a dynamic mechanical thermal analyzer (DMA) at a heating rate of 10°C / min. The result was the transition peak temperature of tanδ in °C;
[0155] (2) Planar thermal expansion coefficient (XY-CTE): A laminate with a length of 60 mm, a width of 4 mm, and a thickness of 0.20 mm was taken as a sample, with the warp direction of the glass fiber in the Y direction and the weft direction of the glass fiber in the X direction. The sample was dried in an oven at 105°C for 1 hour and then cooled to room temperature in a dryer. The measurement was performed using the thermal mechanical analysis method (TMA), with a heating rate of 10°C / min, from room temperature to 300°C, and two heatings were performed. After the first heating was completed and cooled to room temperature, the sample was re-placed for the second heating. The result was the planar thermal expansion coefficient at the second heating from 50°C to 130°C, and the unit was ppm / °C;
[0156] (3) Dielectric constant (D k ) and dielectric loss tangent (D f ): A laminate with a length of 100 mm, a width of 100 mm, and a thickness of 0.20 mm was taken as a sample. The sample was ultrasonically cleaned in deionized water to remove impurities on the surface, and then dried in an oven at 105°C for 1 hour and cooled to room temperature in a desiccator. The dielectric constant (D k ) and dielectric loss tangent (D f );
[0157] (4) Peel strength (PS): A metal foil-clad laminate with a length of 50 mm and a width of 50 mm was taken as a sample. A metal foil test strip with a width of 3.0 mm was prepared on the sample by using a tape method and an etching method. A peel tester was used to apply pressure in a vertical direction at a speed of 50 mm / min to peel the metal foil off the laminate. The peel strength of the metal foil-clad laminate was obtained in N / mm.
[0158] (5) Laminate sub-surface appearance: Visually observe the sub-surface appearance of the laminate. If it is flat and uniform, without dry spots and grooves, it is recorded as "good";
[0159] (6) Storage stability: After 1 day of storage, if the resin of component (A) has no crystallization and the change in gelation time is less than 15%, it is recorded as "good";
[0160] (7) Weight average molecular weight: the test method is GB / T 21863-2008, and it is determined by gel permeation chromatography based on polystyrene calibration;
[0161] (8) Primary amine value: prepare a 0.1 mol / L perchloric acid-acetic acid solution, standardize the concentration with potassium hydrogen phthalate, and record it as C; take an addition reaction product of a maleimide compound a1 containing at least 2 N-substituted maleimide groups in one molecule and an amine compound a2 containing at least 2 primary amino groups in one molecule with a solid content of A, add 50 mL of acetic acid and 5 mL of acetone, and stir until completely mixed; use an automatic potentiometric titrator to titrate with the perchloric acid-acetic acid solution of the standardized concentration, and record the volume of solvent consumed at the end point, which is recorded as V; primary amine value = 10 × C × V / M / A, in mmol / g.
[0162] The test results are shown in Table 3:
[0163] Table 3
[0164]
[0165] According to the performance test data in Table 3, the metal-clad laminates prepared by the resin compositions provided in Examples 1 to 11 of the present invention exhibit excellent dielectric properties, high adhesion to metal foil, dimensional stability and processability, a glass transition temperature of 218 to 295°C, a planar thermal expansion coefficient as low as 7 to 13 ppm / °C, a dielectric constant of 3.85 to 4.31 at 10 GHz, a dielectric loss tangent of 0.0045 to 0.0060, a peel strength of 0.45 to 0.65 N / mm, and a smooth and uniform laminate with no dry spots or grooves on the surface.
[0166] From the performance test data of Examples 1 and 5, it can be seen that polyolefin resin can improve the dielectric properties of the laminate; from the performance test data of Examples 1 and 8, it can be seen that the polyphenylene ether containing vinyl benzyl at the end can improve the glass transition temperature and dielectric properties of the laminate; from the performance test data of Examples 1 and 9, it can be seen that the acrylate compound DCP crosslinking agent of the structure shown in Formula I can synergize with the (A) component and the (B) component to improve the peel strength of the metal foil laminate. If the primary amine value of the (A) component is too high (Example 10), the gelation time of the (A) component will be shortened during storage, affecting the timeliness of the use of the (A) component in the resin composition; if the primary amine value of the (A) component is too low (Example 11), the (A) component will have resin precipitation during storage, which also affects the timeliness of the (A) component in the resin composition.
[0167] If the maleimide compound added with the amine compound a2 containing at least two primary amino groups in one molecule is not used (Comparative Example 6), the planar thermal expansion coefficient of the laminate will increase, and the peel strength of the metal foil-clad laminate will be reduced; if the maleimide compound added with the amine compound a2 containing at least two primary amino groups in one molecule is replaced with an equal weight portion of 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane (Comparative Example 9), the resin adhesive cannot be prepared normally, and thus the prepreg and the metal foil-clad laminate cannot be prepared; if polyphenylene ether is not used (Comparative Example 7), the dielectric properties of the laminate will be reduced, making it difficult to meet the requirements of high-speed applications; if a cross-linking agent is not used (Comparative Example 3), the glass transition temperature of the laminate will be reduced and the peel strength of the metal foil-clad laminate will be reduced.
[0168] If the amount of component (A) is too much (Comparative Example 5), the dielectric properties of the laminate will be reduced, making it difficult to meet the requirements of high-speed applications; if the amount of component (B) is too much (Comparative Example 8), the peel strength and glass transition temperature of the metal-clad laminate will be reduced; if the amount of component (C) is too much (Comparative Example 4), the laminate will not be fully cured, affecting the reliability of the laminate and the metal-clad laminate.
[0169] If the weight ratio of the maleimide compound a1 not participating in the addition reaction and the addition reactant with a weight average molecular weight of less than 1000 to the component (A) is too low (Comparative Example 1), the fluidity of the resin composition deteriorates, the laminate surface appears dry flower defects, and the adhesion between the resin composition and the metal foil decreases; if the weight ratio of the maleimide compound a1 not participating in the addition reaction and the addition reactant with a weight average molecular weight of less than 1000 to the component (A) is too high (Comparative Example 2), the laminate surface appears gully defects (such as Figure 1 The vertical strip grooves at the bottom affect the subsequent processing and use.
[0170] The applicant declares that the present invention uses the above embodiments to illustrate a resin composition and a prepreg and a metal foil-clad laminate comprising the same, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A resin composition, characterized in that The resin composition comprises the following components by weight: (A) 10 to 70 parts of an addition reaction product of a maleimide compound a1 containing at least 2 N-substituted maleimide groups in one molecule and an amine compound a2 containing at least 2 primary amino groups in one molecule; (B) 10 to 70 parts of a polyphenylene ether containing an unsaturated bond; and (C) 5 to 50 parts of a crosslinking agent. The weight of the maleimide compound a1 not participating in the addition reaction and the addition reactant with a weight average molecular weight less than 1000 in the component (A) accounts for 45 to 75% of the component (A); (C) The crosslinking agent includes a crosslinking agent having a carbon-carbon unsaturated double bond in the molecule and / or a cyanate ester.
2. The resin composition according to claim 1, characterized in that The primary amine value of the (A) component is 0.10 to 1.00 mmol / g.
3. The resin composition according to claim 1, characterized in that The maleimide compound a1 contains two N-substituted maleimide groups in one molecule.
4. The resin composition according to claim 1, characterized in that The maleimide compound a1 includes N,N'-ethylenebismaleimide, N,N'-hexamethylenebismaleimide, N,N'-(1,3-phenylene)bismaleimide, N,N'-(1,3-(2-methylphenylene))bismaleimide, N,N'-(1,3-(4-methylphenylene))bismaleimide, N,N'-(1,4-phenylene)bismaleimide, bis(4-maleimidophenyl)methane, bis(3-methyl-4-maleimidophenyl)methane, bis(3,5-dimethyl-4-maleimidophenyl)methane, bis(3- ethyl-5-methyl-4-maleimidophenyl)methane, bis(3-ethyl-4-maleimidophenyl)methane, bis(3,5-diethyl-4-maleimidophenyl)methane, bis(4-maleimidophenyl)ether, bis(4-maleimidophenyl)ketone, bis(4-maleimidocyclohexyl)methane, 1,4-bis(4-maleimidophenyl)cyclohexane, 1,4-bis(maleimidomethyl)cyclohexane, 1,4-bis(maleimidomethyl)benzene, 1,3-bis(4-maleimidophenoxy)benzene, 1,3-bis(3-maleimidophenyl) oxy)benzene, bis(4-(3-maleimidophenoxy)phenyl)methane, bis(4-(4-maleimidophenoxy)phenyl)methane, 1,1-bis(4-(3-maleimidophenoxy)phenyl)ethane, 1,1-bis(4-(4-maleimidophenoxy)phenyl)ethane, 1,2-bis(4-(3-maleimidophenoxy)phenyl)ethane, 1,2-bis(4-(4-maleimidophenoxy)phenyl)ethane, 2,2-bis(4-(3-maleimidophenoxy)phenyl)propane, 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane Any one or a combination of at least two of bis(4-(4-maleimidophenoxy)phenyl)propane, 2,2-bis(4-(3-maleimidophenoxy)phenyl)butane, 2,2-bis(4-(4-maleimidophenoxy)phenyl)butane, 4,4'-bis(3-maleimidophenoxy)biphenyl, 4,4'-bis(4-maleimidophenoxy)biphenyl, bis(4-(3-maleimidophenoxy)phenyl)ketone, bis(4-(4-maleimidophenoxy)phenyl)ketone, bis(4-(3-maleimidophenoxy)phenyl)ether or bis(4-(4-maleimidophenoxy)phenyl)ether.
5. The resin composition according to claim 4, characterized in that The maleimide compound a1 is any one of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, bis(4-maleimidophenyl)methane or 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane or a combination of at least two thereof.
6. The resin composition according to claim 1, characterized in that The amine compound a2 includes a siloxane compound containing at least two primary amino groups, diaminobenzidine, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diethyl-4,4'-diaminobiphenyl, diaminodiphenylmethane, 3,3'-dimethoxy-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminobiphenyl methylmethane, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, diaminodiphenyl ether, 3,3'-dimethoxy-4,4'-diaminodiphenylmethane aminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminodiphenyl ether, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenyl ether, 3,3'-diethyl-4,4'-diaminodiphenyl ether, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenyl ether, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenyl ether, 1,3 - any one of bis(4-aminophenoxy)benzene, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 2,2-bis(4-(3-aminophenoxy)phenyl)propane, 4,4'-bis(4-aminophenoxy)biphenyl, 1,4-bis(4-aminophenoxy)benzene, 2,2'-dimethyl-4,4'-diaminobiphenyl or 4,4'-diamino-3,3'-dihydroxybiphenyl, or a combination of at least two thereof.
7. The resin composition according to claim 6, characterized in that The amine compound a2 is any one of a siloxane compound containing at least two primary amino groups, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, or 2,2-bis(4-(4-aminophenoxy)phenyl)propane, or a combination of at least two thereof.
8. The resin composition according to claim 1, characterized in that The amine compound a2 includes a siloxane compound having two primary amino groups in one molecule.
9. The resin composition according to claim 8, characterized in that The amine compound a2 includes a siloxane compound having two primary amino groups at the molecular terminals.
10. The resin composition according to claim 8, characterized in that Based on 100 parts by weight of the total amount of the component (A), the component (B) and the component (C), the amount of the siloxane compound containing two primary amino groups is 1 to 30 parts.
11. The resin composition according to claim 10, characterized in that The amount of the siloxane compound containing two primary amino groups is 2 to 15 parts.
12. The resin composition according to claim 1, characterized in that The component (B) is a polyphenylene ether having an unsaturated group at the end.
13. The resin composition according to claim 12, characterized in that The unsaturated group includes any one of vinylbenzyl, vinylphenyl or acrylate groups or a combination of at least two of them.
14. The resin composition according to claim 1, characterized in that The crosslinking agent having carbon-carbon unsaturated double bonds in the molecule includes any one or a combination of at least two of multifunctional vinyl compounds, allyl compounds, acrylate compounds, trialkenyl isocyanurate compounds, maleimide compounds, acenaphthylene compounds or polybutadiene.
15. The resin composition according to claim 14, characterized in that The trialenyl isocyanurate compound includes triallyl isocyanurate.
16. The resin composition according to claim 14, characterized in that The acrylate compound includes an acrylate compound having a structure as shown in Formula I: Wherein, R1 is independently selected from C1-C20 straight chain or branched alkylene; R2 is independently selected from hydrogen, C1-C20 straight chain or branched alkyl.
17. The resin composition according to claim 1, characterized in that Based on 100 parts by weight of the total amount of the (A) component, the (B) component and the (C) component, the (A) component is used in an amount of 10 to 60 parts.
18. The resin composition according to claim 1, characterized in that Based on 100 parts by weight of the total amount of the (A) component, the (B) component and the (C) component, the (B) component is used in an amount of 10 to 60 parts.
19. The resin composition according to claim 1, characterized in that Based on 100 parts by weight of the total amount of the (A) component, the (B) component and the (C) component, the (C) component is used in an amount of 5 to 30 parts.
20. The resin composition according to claim 1, characterized in that The resin composition further comprises 5 to 30 parts by weight of polyolefin resin.
21. The resin composition according to claim 1, characterized in that The resin composition further comprises 0.01 to 5 parts by weight of a curing accelerator.
22. The resin composition according to claim 21, characterized in that The curing accelerator includes any one of an acidic curing accelerator, an organic phosphorus curing accelerator, an imidazole curing accelerator, a pyridine curing accelerator, an amine curing accelerator, a peroxide or an organic metal salt, or a combination of at least two thereof.
23. The resin composition according to claim 1, characterized in that The resin composition further comprises 5 to 250 parts by weight of inorganic filler.
24. The resin composition according to claim 1, characterized in that The resin composition further comprises 0.01 to 10 parts by weight of a coupling agent.
25. The resin composition according to claim 24, characterized in that The coupling agent includes a silane coupling agent.
26. A prepreg, characterized in that The prepreg comprises a substrate, and the resin composition according to any one of claims 1 to 25 attached to the substrate by impregnation and drying.
27. The prepreg according to claim 26, characterized in that The substrate includes any one of glass fiber cloth, organic fiber cloth or glass fiber paper.
28. A metal foil-clad laminate, characterized in that: The metal foil-clad laminate comprises at least one prepreg according to claim 26 or 27, and a metal foil disposed on one side or both sides of the prepreg.
29. The metal-clad laminate according to claim 28, characterized in that: The metal foil is copper foil.
30. A printed circuit board, characterized in that: The printed circuit board includes at least one prepreg according to claim 26 or 27 or the metal foil-clad laminate according to claim 28 or 29.
Citation Information
Patent Citations
Thermosetting resin composition, prepreg comprising same, metal-foil-coated laminate and printed circuit board
CN109825081A
Modified polyphenylene ether resin, thermosetting resin composition and application thereof
CN109988298A
Hydrocarbon resin composition as well as preparation method and application thereof
CN111154197A
Resin composition, prepreg, laminated board, metal foil cladded laminated board and printed circuit board
CN110218415A
Thermosetting resin composition and prepreg, laminated board and metal foil-clad laminated board using thermosetting resin composition
CN113088061A